Corticotomy as a stage of complex treatment of orthodontic patients - A. R. Sergeenkova; N. S. Drobysheva (Эндодонтия Today)
Aim. To evaluate the effectiveness of the method of corticotomy with bone grafting with narrowing of the upper jaw for its expansion. Materials and methods. A clinical case of a 35-year-old patient with a narrowing of the upper jaw is presented. The transversal size of the jaw was measured using a CT scan using the analysis of the University of Pennsylvania. The patient also underwent an analysis of the inclination of the molars and an assessment of the thickness of bone tissue before and after corticotomy. Results. The results showed that after corticotomy with bone grafting, skeletal expansion of the upper jaw occurred in patient V. Conclusions. As a result of the conducted research, this method has confirmed its effectiveness and has several advantages. Accordingly, in certain clinical cases, you can limit yourself to this method, excluding surgical expansion of the upper jaw with the installation of a distraction device.